2005
DOI: 10.1016/s0753-3322(05)80019-8
|View full text |Cite
|
Sign up to set email alerts
|

Yearly and perhaps transyearly human natality patterns near the equator and at higher latitudes

Abstract: Data on the daily numbers of births in Davao, Philippines, available from 1993 to 2003 are re-analyzed herein by linear-nonlinear rhythmometry, as are data from Italy and Japan. A transyear, characterizing the solar wind and other non-photic physical environmental factors, corresponds to a spectral peak of the near-equatorial natality series. This component with a period of about 1.3 years is found to have an amplitude larger than the calendar year, the amplitude ratio being 134%. Whereas the transyear is vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In their analysis of cerebral malaria in Papua New Guinea (latitude between 0° and 12°S, longitude 140°-160°E), these authors also reported the presence of a strong calendar-yearly component, in the absence of a marked transyear. By contrast, a transyear over calendar year prominence at -3° from the equator characterized a time series of natality in Mindanao, Philippines (8°N, 125°E) [2,3]. In a study of malaria in Thailand, a period of about 4 years was prominent, while geographic differences prevailed; "seasonal" cycles were only synchronous in small clusters [9].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In their analysis of cerebral malaria in Papua New Guinea (latitude between 0° and 12°S, longitude 140°-160°E), these authors also reported the presence of a strong calendar-yearly component, in the absence of a marked transyear. By contrast, a transyear over calendar year prominence at -3° from the equator characterized a time series of natality in Mindanao, Philippines (8°N, 125°E) [2,3]. In a study of malaria in Thailand, a period of about 4 years was prominent, while geographic differences prevailed; "seasonal" cycles were only synchronous in small clusters [9].…”
Section: Introductionmentioning
confidence: 96%
“…Signatures of cycles in the sun's and the earth's magnetism, found in the aetiology of both communicable and non-communicable diseases, are selectively assorted geographically [1]. Far-transyears and near-transyears (components with periods a few months or a few weeks longer than the calendar year, respectively) are both known to characterize interplanetary and terrestrial magnetism and their biospheric signatures [1][2][3]. A geographic study of the incidence of sudden cardiac death reveals the prominence of the transyear over the calendar year in Minnesota and Tokyo, whereas the opposite holds in Hong Kong, North Carolina (USA), and the Republic of Georgia [2,4].…”
Section: Introductionmentioning
confidence: 99%